Challenges when introducing electronic exam - Matti Kuikka; Markus Kitola; Mikko-Jussi Laakso (Association for Learning Technology, 2014)
Time pressures often necessitate the use of more efficient exam tools, such as electronic exams (e-exams), instead of traditional paper exams. However, teachers may face challenges when introducing e-exams in a higher education context. This paper describes what kinds of challenges teachers may face when introducing e-exams, based on experiences in Turku University of Applied Sciences (TUAS) where e-exams have been used since 2012. For this research, the authors used their personal experiences as administrators and teachers of current e-systems used for e-exams in universities in Turku, Finland. Quantitative data were collected by survey from teachers in TUAS (the case study). The learning management systems, Moodle, Optima and ViLLE, and dedicated e-examination systems, Soft Tutor and Tenttis, were also compared to clarify what kind of features are available in order to ease teachers' work with examinations. The results identified various challenges during e-exam introduction in TUAS. The paper also provides a list of essential services or features for teachers to ease the introduction of e-exams. Among the analysed systems, ViLLE supported most of the required features, and can be used for both learning management and e-examination systems, providing teachers with one single system, which was found to be important to teachers. The key service found by this paper is 'support for teachers', which is in line with previous studies.